Applications of X-ray and Medical Imaging Techniques in Early Detection of Cancerous Tumors: A Comparative Study Between X-ray, MRI, and CT Scanning - Hossein Falih hassouni; Tabarak Shaker Kazim; Maha Adi Abdul Hadi Kazim; Noor Mohammed Khader; Raghad Aamer Jawad (American Journal of Botany and Bioengineering, 2025)
Early detection of cancer significantly improves treatment outcomes and survival rates. However, limitations in current imaging modalities create challenges in accurately identifying tumors at initial stages. This study addresses the knowledge gap by comparing X-ray, Magnetic Resonance Imaging (MRI), and Computed Tomography (CT) scanning for cancer detection. A systematic analysis was conducted to evaluate the accuracy, advantages, and limitations of each modality across different cancer types. Findings reveal that X-ray remains a widely used and cost-effective screening tool, while MRI provides superior soft tissue contrast and CT offers detailed cross-sectional imaging. The results suggest that combining multiple imaging techniques enhances diagnostic accuracy and early tumor identification. The study underscores the importance of advancing imaging technology and integrating artificial intelligence to improve cancer diagnostics.